The Role of the Health Belief Model in Antenatal Care Visits among Pregnant Women at Sentru Saude Komunitaria, Baucau Municipality, Timor Leste - Natalino de Jesus Varela; Yulia Lanti Retno Dewi; Bhisma Murti; Revi Gama Hatta Novika; Setyo Sri Rahardjo (Journal of Health Promotion and Behavior, 2026)
Background: Antenatal Care (ANC) visits are an essential intervention for reducing the risk of maternal morbidity and mortality. However, ANC coverage in several regions of Timor-Leste, including Baucau Municipality, remains below the national target. This study aimed to analyze factors influencing pregnant women’s compliance with recommended ANC visits according to timing and guidelines using the Health Belief Model (HBM)Subjects and Method: This cross-sectional study involved 200 pregnant women registered at healthcare facilities in Baucau Municipality, Timor-Leste. Data were collected using a question-naire based on HBM constructs that had been tested for validity and reliability. Data were analyzed using path analysis with STATA version 13 to identify direct and indirect effects among variables associated with ANC visits.Results: The results showed that cues to action had a direct and positive effect on ANC visits (b= 0.12; 95% CI= 0.03 to 0.20; p= 0.005). Gestational age had a significant positive effect on ANC visits (b= 0.24; 95% CI= 0.16 to 0.32; p< 0.001). In contrast, distance to healthcare facilities had a significant negative effect (b= -0.70; 95% CI= -0.75 to -0.64; p< 0.001), while parity had a negative but non-significant effect (b= -0.05; 95% CI= -0.14 to 0.03; p= 0.175). Self-efficacy had an indirect effect on ANC visits through perceived benefits (b= 0.15; 95% CI= 0.01 to 0.29; p= 0.040) and perceived benefits also had a significant indirect effect (b= 0.22; 95% CI= 0.08 to 0.37; p= 0.002). Perceived severity indirectly influenced ANC visits as well (b= -0.14; 95% CI= -0.26 to -0.01; p= 0.035).Conclusion: ANC visits increased with stronger cues to action and advancing gestational age. Conversely, ANC visits decreased with greater parity and longer distance to healthcare facilities. ANC visits were indirectly influenced by perceived susceptibility, perceived severity, perceived barriers, perceived benefits, and self-efficacy.